An analysis method for control reconfigurability of linear systems. Issue 1 (1st January 2016) - Wang, Dayi; Duan, Wenjie; Liu, Chengrui
Abstract: The reconfigurability of control systems is further researched based on the function-objective model ( FOM ). The establishment of the FOM has been published in the authors' former paper, solving the problem whether the system is reconfigurable without losing the desired control objective. Based on the FOM, the importance factor, the risk factor and the k th reconfigurability factor are proposed to evaluate the fault risks of all components and the system reconfigurability with k faults. These factors show which components should be improved and which faults cannot be tolerated. The analysis results are very useful for enhancing the fault-tolerance performances of the control systems by improving system designs. A satellite model is utilized to illustrate the proposed method.